XRD and impedance spectroscopy study of phase transitions in nanocrystalline Li-Mn spinels - Lisovytskiy, D.V.; Baumer, V.N. (Functional Materials, 2007)
Phase transition in nanocrystalline lithium manganese spinels synthesized by sol-gel technique in laboratory and in commercially available LiMn₂O₄ powders was studied. In addition to the standart impedance measuments of impedance spectrum and X-ray pattern in non-focusing geometry were performed in the temperature range between -25 and +100°C. Using Rietveld refinement, the phase composition of samples has been estimated quantitatively.